Metallic‐Glass Nanostructures: Tunable Hierarchical Metallic‐Glass Nanostructures (Adv. Funct. Mater. 21/2013). (3rd June 2013) - Mukherjee, Sundeep; Sekol, Ryan C.; Carmo, Marcelo; Altman, Eric I.; Taylor, André D.; Schroers, Jan
<x xml:space="preserve">Abstract</x> Palladium‐rich nanostructures with widely different morphologies are obtained by electrochemical processing of a nickel‐palladium metallic glass. Metallic glasses are multicomponent alloys that exist in a wide range of chemical compositions and have a fully amorphous structure. On page 2708, Sundeep Mukherjee and co‐workers report that starting with a homogeneous and isotropic amorphous surface, the morphology and chemistry can be modified to obtain hierarchical nanostructures with high catalytic activity. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>